A Multi-locus Molecular Phylogeny of the Core Genera of Ellescini (Coleoptera: Curculionidae: Curculioninae) with a Review of the Species of Ellescus in North America - Lewis, Jake (Université d'Ottawa / University of Ottawa, 2022)
A combination of morphological and molecular techniques were used to investigate the taxonomy of th species of Ellescus Dejean, 1821 in North America (Curculionidae: Curculioninae: Ellescini), as well as investigate the phylogenetic relationships amongst genera within the tribe Ellescini. Four valid species of Ellescus were documented from the Nearctic Region. These include the temperately distributed E. michaeli n. sp., the west coast endemic species E. californicus (Casey, 1885) (resurrected from synonymy with E. ephippiatus (Say, 1831)), the widespread, hypervariable E. ephippiatus, and the Holarctic E. bipunctatus (Linnaeus, 1758) (of which E. borealis (Carr, 1920) is found to be a junior synonym). The European species, E. scanicus (Paykull, 1792), is determined to have been erroneously reported from North America. The Maximum Likelihood and Bayesian Inference analyses based on CO1, CytB, 28S, and 16S sequence data found moderate to strong support for the monophyly of Ellescus and moderate to strong support for Proctorus LeConte, 1876 as a lineage nested within Dorytomus Germar, 1817. The genera Proctorus and Rodotymus Zumpt, 1932 are placed in synonymy under Dorytomus.
Keywords: Weevil; Taxonomy; Systematics; Ellescini